REPRESENTATION OF SOCIAL CRITICISM IN AN EPISODE OF INDONESIAKU TITLED “WE ARE THE ISOLATED ONES AT THE END OF THE COUNTRY” - Yudha Asmara Dwi Aksa; Abdul Haris; Silfani Hariska (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
Social criticism is a way to express opinions and functions as a social control while criticizing a problem in society. In this regard, television show can be used to convey social criticism as it has a strong effect for influencing people's minds and change the audience's point of view. Indonesiaku is a documentary TV show that explores the problems in remote villages in Indonesia such as the lack of infrastructure development or the social welfare of Indonesian people. One of Indonesiaku’s episodes titled “WE ARE THE ISOLATED ONES AT THE END OF THE COUNTRY” represents underprivileged people in Baibunta Hamlet and Lelogama Village. The episode shows the lack of access to those areas which hamper the distribution of goods to those villages. This episode can be perceived one of social criticisms toward Indonesian government. Thus, the present study aims to analyze how the aforementioned episode shows social criticism using the semiotic theory from Pierce. The present study analyzes the selection of environmental settings, situations and narratives in the contexts of social criticism. The results of this study explain that the social criticism in Indonesiaku shows is a satirical one and displayed through visuals and narration. The results also suggest that the lack of infrastructure development in Baibunta Hamlet and Lelogama Village as the cause of poverty in those villages.